A spatially pinned surface plasmon through short-circuiting electronic oscillation in waveguide-sustained SPPs. Issue 42 (23rd October 2020) - Fu, Yulan; Zhang, Xiaochen; Wang, Meng; Zhang, Xinping
Abstract : A spatially pinned surface plasmon is constructed by connecting a gold nanoshell grating with a planar gold nanofilm, forming a periodical array of gold nanoloops. Abstract : A spatially pinned surface plasmon is constructed by connecting a gold nanoshell grating with a planar gold nanofilm, forming a periodical array of gold nanoloops. Dramatic electric field modulation and high charge carrier density on the contact sites enable balanced plasmonic electron distribution over the spatially pinned nanostructures. Compared with its counterpart, spacer-supported double-layer surface plasmon polaritons (SPPs), the pinned structure not only changed the electronic oscillation channels but also short-circuited the propagating SPPs at the top and bottom interfaces. Ultrafast spectroscopic dynamics identified a much-extended relaxation lifetime of the pinned plasmon and revealed a holding time as long as 1.3 ps for the double-layer SPPs, which was sustained by microcavities based on distributed optical feedback. These results introduced a new type of surface plasmon and a new design of time retarders for optical logic circuits.